Motivational Structure in Education (R&E-SOURCE, 2018)
The article focuses on the importance of motivation in foreign language education. The aim of the paper is to analyse the motivational structure towards the foreign language learning in context of the factors of wider social environment in which teaching and learning takes place. The sample of the survey were pupils from three primary schools in Slovakia who learn German language as the obligatory subject according to the school education program. The survey is based on the statistical analysis of the dimensions of the motivational structure, depending on schools and classes attended. The results confirmed the diversity in student motivation among schools. The differences in both intensity and constellation of the motivational structure were recorded. The research findings point to a dynamic link between the participants of the educational process and the wider social context factors.